Evaluation of Malnutrition and Quality of Life in Patients Treated for Oral and Oropharyngeal Cancer - Shruthi Pingili; Junaid Ahmed; Nanditha Sujir; Nandita Shenoy; Ravikiran Ongole (The Scientific World Journal)
Background. Oral and oropharyngeal cancer is a debilitating disease with high morbidity and mortality. Depending on the site and extent of the involvement of the cancer and the type of treatment modality, these patients can develop pain, trismus, xerostomia, dysphagia, and taste disturbances, compromising them socially and nutritionally. The aim of the study was to evaluate malnutrition and quality of life in patients treated for oral and oropharyngeal cancer. Methodology. A cross-sectional study was conducted which included 97 patients treated for oral and oropharyngeal cancer. The quality of life of the selected patients was assessed by using a validated European Organization for the Research and Treatment of Cancer’s Quality of Life Questionnaire, Head and Neck and Mandibular Function Impairment Questionnaire. Pre- and posttreatment weight of the patients were assessed, and weight loss of ≥10% of pretreatment weight was considered as malnutrition. The chi-square test was used to correlate the symptoms with the quality of life. A paired t test was used to assess the differences in weight before and after treatment, and a p value of <0.005 was considered as significant. Results. The most commonly reported symptoms were xerostomia (93.81%), pain (81.44%), and dysphagia (76.3%). A total of 40.2% of the individuals in the study had malnutrition. Malnutrition was comparatively lower in the group who had nutritional supplements. Conclusion. The quality of life in patients treated for oral and oropharyngeal cancer deteriorates immediately after the treatment; however, it significantly improves over time.